Detraining effect on cardiac autonomic response to an all-out sprint exercise in trained adolescent swimmers - Ruiz-Navarro, J. J.; Plaza-Florido, A.; Alcantara, J. M. A.; Gay, A.; Arellano, R. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study aimed to investigate the effects of a 5-week training cessation on the cardiac autonomic response after a 50-m swimming time-trial test.